Sources and sinks of N2O in the subtropical Jiulong River Estuary, Southeast China - Li, Yuhong; Luo, Yang; Liu, Jian; Ye, Wangwang; Zhang, Jiexia; Zhan, Liyang (Frontiers in Marine Science, 2023)
Nitrous oxide (N2O) is one of the most important greenhouse gases and contributes to the depletion of ozone in the stratosphere. Estuaries are areas of intensive biological production and associated N2O emissions through both denitrification and nitrification processes. The spatial and temporal variations of N2O in the Jiulong River Estuary, a subtropical estuary, were explored to evaluate sources and sinks of N2O in this area. The estuary was found to be a strong source of N2O, its saturation in the surface water ranged from 113 to 2926% relative to the ambient atmospheric concentrations, showing great temporal and spatial variations and was influenced by multiple factors such as the concentration of dissolved inorganic nitrogen (DIN, i.e., NO3-, NH4+ and NO2-), salinity and dissolved oxygen. N2O concentrations were at a high level in upper estuary but reduced to the lower parts of the estuary. Groundwater input could be another contributor to N2O in the estuary. Almost all N2O within the estuary was released into the atmosphere rather than being transported to the bay. The N2O flux in the estuary (mean 597 μmol/m2/d) was at the higher end of the range observed in estuaries worldwide due to the very high DIN loads in the Jiulong River Estuary. Our data indicate that the N2O saturation in the estuary continues to increase, although the DIN inputs began to decline in 2011, which might be relate to the improved environmental conditions with increased oxygen concentrations. N2O production pathways have changed from predominantly denitrification in the past toward significant production from nitrification in the present. Further investigation is needed to better understand the behavior of N2O in the Jiulong River Estuary.